Tracking Landscape-Scale Movements of Snow Buntings and Weather-Driven Changes in Flock Composition During the Temperate Winter - Mckinnon, Emily A.; Laplante, Marie-Pier; Love, Oliver P.; Fraser, Kevin C.; Mackenzie, Stuart; Vézina, François (Frontiers in Ecology and Evolution, 2019)
Nomadic movements of migratory birds are difficult to study, as the scale is beyond what is possible using hand-held telemetry (10s of kms) but too small for tracking devices like geolocators (50-100km accuracy). Recent widespread installation of automated telemetry receiving stations allowed us, for the first time, to quantify and test predictions about within-winter movements of a presumed nomadic species, the Snow Bunting (Pletrophenax nivalis). We deployed coded radio-transmitters on 40 individual Snow Buntings during two winters (2015-16 and 2016-17) in southern Ontario, Canada, and tracked movements over a 300 km by 300 km area with 69-77 active radio-receiving stations (Motus Wildlife Tracking Network). To complement our tracking data, we also examined the influence of weather on within-season changes in flock composition (i.e., sex and age ratios) at a single wintering site over 6 consecutive years (n = 9312). We recorded movements of 25 individuals from the deployment sites to 1-6 different radio receiving locations (mean 2.68 locations/bird). Birds travelled a minimum average distance of 49 km between detections (range: 3km to 490km) in the core wintering period of Dec-Feb, and cumulative total movements ranged from 3km to 740km (average cumulative distance 121  46km). In March distances between detections increased to an average of 110km, suggesting an extended early-migration period. Overall, older birds (after-second year or older) tended to move more (higher cumulative distances travelled) than younger (first winter) birds, even during the Dec-Feb period. The long-term banding data revealed that larger, male birds were more likely to be captured in colder and snowier weather, relative to female and smaller birds, suggesting that they can withstand these conditions more easily owing to their body size. We have provided the first direct-tracking data on nomadic winter movements of Snow Buntings, and tested the hypothesis that winter weather drives flock composition at a single site. Site-specific banding data suggest that weather-related changes in flock composition could explain the nomadic, landscape-scale movements of Snow Buntings we observed by using automated telemetry. Future work should explore the importance of resource availability, competition, and predation risk as drivers of winter movements in Snow Buntings.